Digital Database Training for Sheep-Fattening Data Management: A Training Report - Wamatu, Jane; Ekule, Muluken (International Center for Agricultural Research in the Dry Areas, 2023)
A training conducted on the use of the performance recording system, Dtreo platform, for crowdsourcing of sheep fattening data in Ethiopia.